2012
DOI: 10.1021/pr300700e
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Royal Jelly and Characterization of the Functions of its Derivation Glands in the Honeybee

Abstract: To identify candidate royal jelly (RJ) proteins that might affect the physiologic status of honeybee colony members, we used shotgun proteomics to comprehensively identify the RJ proteome as well as proteomes of the hypopharyngeal gland (HpG), postcerebral gland (PcG), and thoracic gland (TG), from which RJ proteins are assumed to be derived. We identified a total of 38 nonredundant RJ proteins, including 22 putative secretory proteins and Insulin-like growth factor-binding protein complex acid labile subunit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 64 publications
8
91
1
1
Order By: Relevance
“…In the recently compiled honeybee protein atlas of Chan et al [49] MRJPs were shown to occur in various organs of the abdomen but not in the thoracic muscle and the thoracic salivary gland (see also [25]). Nevertheless, various MRJPs, except for MRJP4, 6 and 8, were identified in the honeybee’s nerve chord [49] that is crossing the thorax and abdomen [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recently compiled honeybee protein atlas of Chan et al [49] MRJPs were shown to occur in various organs of the abdomen but not in the thoracic muscle and the thoracic salivary gland (see also [25]). Nevertheless, various MRJPs, except for MRJP4, 6 and 8, were identified in the honeybee’s nerve chord [49] that is crossing the thorax and abdomen [3].…”
Section: Discussionmentioning
confidence: 99%
“…Already Peiren et al [50,51] showed that both proteins are not constrained to the food glands but also present in bee venom. In fact, MRJP8 has never been identified as component of RJ in A. mellifera and also MRJP9 was only identified in three out of numerous studies on the RJ proteome [20,24,25] alluding to a low amount of the protein in RJ. This is well in line with the previous notion that mrjp1-7 derived from mrjp8 and 9 during honeybee evolution [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is an exclusive food for adult queens throughout their life (Fujita et al, 2013). The induction of larval development into queen has been ascribed to major royal jelly proteins (MRJPs) and a 57-kDa protein known as royalactin (Kamakura, 2011; Buttstedt et al, 2013), although contrary opinions have been raised against the alleged role of this latter (Buttstedt et al, 2016).…”
Section: Royal Jellymentioning
confidence: 99%
“…Royal jelly (RJ) is a yellow or pale syrup-like substance which is secreted by the hypopharyngeal and mandibular glands of young honey bees (“nurses”) mainly for feeding the queen larvae and adults (Fujita et al, 2012). Worker destined larvae (younger than 3 days old) will develop into queen if they are fed with RJ in queen cells.…”
Section: Introductionmentioning
confidence: 99%